Factors associated with behavioral euthanasia in pet dogs - Hitchcock, Miranda; Workman, Miranda K.; Guthrie, Adeline P.; Ruple, Audrey; Feuerbacher, Erica N. (Frontiers in Veterinary Science, 2024)
When pet dogs demonstrate certain serious problem behaviors, this may lead owners to choose behavioral euthanasia. However, research on behavioral euthanasia of pet dogs is sparse and previously published papers have not specifically sampled owners who made the decision to euthanize for behavior. The Behavioral Euthanasia in Pet Dogs Questionnaire was created to collect a wide range of information from dog owners who made behavioral euthanasia decisions. Using this survey, we explored the types of behaviors associated with behavioral euthanasia. Human-directed aggression, especially toward adults living in the household, was the most frequently reported reason for choosing behavioral euthanasia; followed by aggression toward other animals, especially other dogs living in the same household. The majority of dogs displaying human-directed or other animaldirected aggression were reported to have bitten and broken skin, and many of these had bitten in multiple or severe incidents. Most dogs had lived in their homes and displayed problem behaviors for over a year prior to behavioral euthanasia, and the euthanasia occurred at a variety of ages, from less than one year old to 18 years old. Additional research is required to understand environmental or nonbehavioral factors contributing to the behavioral euthanasia of companion animals, as well as the psychosocial and emotional impact of behavioral euthanasia on the human experience. Understanding the behavioral factors associated with behavioral euthanasia can direct resources toward problem behavior interventions, improve public education about animal behavior, and strengthen the human-animal bond.